The Realization of Brown’s Theory of Assessing Reading on Reading Section of English National Examination - Zahratun Nufus; Nur Ifadloh (SALEE: Study of Applied Linguistics and English Education, 2021)
This study is concerned with the realization of Brown’s theory of assessing reading on the English national examination. This study focused on the English national examination for junior high schools in the academic year 2018/2019. It aimed to know what types of assessing reading were used and what the most dominant types were used on the English national examination based on the realization of Brown’s theory. The qualitative approach was employed. The method of analysis used was descriptive research. Based on the data analysis, there was only one type of the four types of reading assessment which was implemented on the English national examination. It was interactive reading. The tasks which were used in interactive reading are impromptu reading plus comprehension question as many as 49 questions which are included in 17 texts and ordering tasks as many as 1 question which was included into 1 text. All of them were spread into 17 texts. The most dominant type of assessing reading was interactive reading (50 questions) which consisted of 49 questions of impromptu reading plus comprehension questions and 1 question of ordering tasks.